GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI MAHASISWA KLUSTER KESEHATAN DAN KLUSTER SAINTEK UNIVERSITAS GADJAH MADA - , INTAN RIZQI R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
If self medication done rationally, it will give many benefits and vice versa. It was expected that if self medication knowledge of university students is high, society knowledge about self medication will also improve. Hence, a research to overview UGMâs students level of self-medication knowledge that differentiated according to cluster, gender and level of study were needed. A cross sectional study was conducted on 110 health cluster students and 101 technology and science cluster students. Those sample sizes were determined by accidental sampling method. Data which were obtained through a questionnaire then described descriptively and analyzed statistically with Spearman Rank Correlation and chi square test. The result showed that 70,91% health cluster students had high self-medication knowledge and 29,09% had poor self medication knowledge. On technology and science cluster students, 24,75% had high self medication and 75,25% had poor self medication. In general students who had high self medication knowledge is health cluster students 70,91%, mostly woman 61,24%, 3rd year students (2011) and from faculty of medicine. There was significant correlation between self medication level of knowledge and demography factors such as gender and year of study (p value = 0,00).